NEET Youth in the Aftermath of the Crisis - Challenges and Policies - Minea, Andreea; Carcillo, Stephane; Fernandez, Rodrigo; Königs, Sebastian (OECD publishing, 2015)
This paper presents an overview of the situation of youth in OECD countries since the onset of the financial crisis focusing primarily on describing the characteristics and living conditions of young NEETs. It also provides data on the availability, coverage and effectiveness of income-support policies for young people, and summarises available evidence on the impact of interventions that aim at improving the social, education and employment situation of the most disadvantaged youth. Due to the paper’s explicit focus on the hardest-to-place, most disadvantaged youth, the range of policies covered is broader than in earlier studies on the same topic, including various social benefits and in-kind services targeted at this group. The paper shows that NEET rates have not yet recovered from the crisis. There are large differences in youth unemployment and inactivity across countries, and these differences were further exacerbated by the recession. Reducing NEET rates is a great challenge for governments, as youth who remain jobless for long periods typically come from more disadvantaged backgrounds, have low levels of educational attainment, and are in many cases inactive. There is substantial evidence, however, that even the most disadvantaged youth can benefit from a variety of targeted interventions, including for instance special education programmes and mentoring.
OECD Social, Employment and Migration Working Papers
Keywords: Education and Training; Children -- Adolescents and youth; Employment -- Unemployment; Disadvantage; Adolescents and youth; Labour market; Learning, education and training; Children; Employment; Education and Training; Disadvantage; Unemployment; Adolescents and youth; Learning, education and training; Employment and unemployment; Adolescents and youth